Inhalation with intravenous loading dose of colistin in critically ill patients with pneumonia caused by carbapenem-resistant gram-negative bacteria. (October 2019) - Choe, Junsu; Sohn, You Min; Jeong, Suk Hyeon; Park, Hyo Jung; Na, Soo Jin; Huh, Kyungmin; Suh, Gee Young; Jeon, Kyeongman
Background: Despite the increasing use of colistin in clinical practice, the optimal dosing, and administration route have not been established. This study aimed to evaluate the clinical outcome and safety of intravenous (IV) colistin with a loading dose (LD) and adjunctive aerosolized (AS) colistin administration in critically ill patients with hospital-acquired pneumonia (HAP) or ventilator-associated pneumonia (VAP) caused by carbapenem-resistant gram-negative bacteria (CRGNB). Methods: We retrospectively reviewed 191 critically ill patients who received colistin for the treatment of HAP or VAP caused by CRGNB. Patients were divided into three groups: non-LD IV (patients received only IV colistin without LD), LD IV (patients received only IV colistin with LD), and AS–LD (patients received IV colistin with LD and adjunctive AS colistin). Results: There was no difference in clinical response between the three groups. However, the rate of microbiological eradication was significantly higher in the AS–LD group (60%) than in the non-LD IV (31%), and LD IV (33%) groups ( p  = 0.010). Patients treated with adjunctive AS colistin in combination with LD IV had significantly lower 30-day mortality rates than patients treated with IV colistin alone ( p  = 0.027). After adjusting for potential confounding factors, adjunctive AS colistin was still significantly associated with lower mortality (adjusted OR 0.338, CI 95% 0.132–0.864, p  = 0.024). However, nephrotoxicity did not change according to the use of LD regimen and AS colistin administration ( p  = 0.100). Conclusions: Adjunctive AS colistin in combination with IV colistin with LD was related to an improved 30-day mortality and microbiological outcome without an increase in nephrotoxicity in critically ill patients with HAP and VAP caused by CRGNB. The reviews of this paper are available via the supplemental material section.